The impact of HRM practices on the employee intention to stay in the Jordanian telecommunications companies - Mohd Hammad, Qatamin Liana; Juhdi, Nurita; Fontaine, Rodrigue Ancelot Harvey (Human Resource Management Academic Research Society (HRMARS), 2023)
In Jordan telecommunications sector considered as one of the main contributors to the Jordan economic growth. Despite this achievement, telecommunication companies in Jordan face various challenges and issues. Employee intention to stay (ITS) is one of the challenges that telecommunication firms face, due to the high turnover rate of employees in Jordanian telecommunications companies over time. Particularly that identifying techniques to encourage employees to stay in the firm has become a key concern because staff retention is a problem that companies face due to the danger of excessive employee turnover. The phenomena alarmed the concern over the turnover issue of telecommunications sector. Employee turnover issue requires implementing good HRM (Human Resource Management) practices in delivering results at the employee level such as a reduction in the likelihood of employee turnover and an increase in their willingness to stay with the company. This paper deliberates the importance of adapting effective HRM practices (performance appraisal, compensation, and training and development practices) to strengthen employee’s retention in the telecommunication companies in Jordan